Pharmacy availability of emergency contraception in southwestern Pennsylvania: A simulated patient study - Katherine Orr; Jennifer Chin; Maris Cuddeback; Jessica Zimo; Colleen Judge-Golden; Marian Jarlenski; Sonya Borrero (Contraception: X, 2021)
Objective: To assess the availability of oral emergency contraception in southwestern Pennsylvania pharmacies. Study design: We conducted a simulated patient study to assess on-the-shelf availability of levonorgestrel emergency contraception and immediate availability of ulipristal acetate emergency contraception. Results: Only 44% of pharmacies stocked levonorgestrel on-the-shelf and only 5% of pharmacies had ulipristal acetate immediately available. Conclusions: We found significant barriers to obtaining timely oral emergency contraception in southwestern Pennsylvania. Implications statement: Timely access to emergency contraception is important for people's ability to determine if, when, how, and under what circumstances to have children. Pharmacies in southwestern Pennsylvania need to expand access to oral emergency contraception.